Abnormal Return Analysis of Heatwave Announcement in China Has the Potential to Increase Indonesia's Coal Exports in Bumi and Adro Stocks - Lea Fathra Azha Nabiela; Lifatin Nada; Darmawan Darmawan (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2023)
This study aims to determine the heatwave announcement in China can increase Indonesia's coal export potential. On the abnormal Return on shares of PT Bumi Resource Tbk (BUMI) and PT Adaro Energy Indonesia Tbk (ADRO). The method used to analyze this research is an event study. Hypothesis testing was carried out using normality tests, paired sample t-tests and one-sample T-tests. From the results of this study, it was found that there was no significant abnormal difference in return after the announcement was published. Therefore, the results were obtained that the published announcement did not contain information for investors because there was no abnormal return around the event.